Comparison of Gonadotropin with Gonadotropin and Letrozole Combination in Infertile Women with Biopsy - Proven Endometriosis Undergoing Intracytoplasmic Sperm Injection - Burak Tanır; Mehmet Serdar Kütük; Mehmet Dolanbay; Mahmut Tuncay Özgün; Semih Uludağ; Ercan Aygen; Yılmaz Şahin (Medical Network, 2016)
OBJECTIVE: To compare the result of intracytoplasmic sperm injection cycles using gonadotrophins with those of using gonadotrophins combined with letrozole in infertile woman with biopsy-proven endometriosis. STUDY DESIGN: This prospective randomized study was performed at the department of Obstetrics and Gynecology Reproductive Center, in Erciyes University. Thirty- three women undergoing intracytoplasmic sperm injection (ICSI) with gonadotropin or combination of gonadotropin with letrozole were accepted. The patients were grouped as: gonadotropin group (Group 1), and gonadotropin plus letrozole (Group 2). Total and clinical pregnancy ratios, length of cycles, and doses of gonadotropin used were compared. RESULTS: Total doses of gonadotrophins used in group 1, and group 2 were 2700 (1800- 3600) IU and 2100 (1575- 3475) IU, respectively. Total dose of gonadotropin used in group 2 was found to be lower than that of group one and this difference was statistically significant (p= 0.002). Stimulation times in group 1 and 2 were 10 (9- 12) day, and (7- 12) day, respectively, and the difference was statistically significant (p=0.048). Number of the retrieved oocytes were higher in group 2 than Group 1(p=0.027). There was no statistically significant difference between groups with regard to numbers of embryos, total and clinical pregnancy ratio. CONCLUSIONS: Letrozole has no effect on the results of ICSI success in infertile women with biopsy proven- endometriosis. However, it reduces the gonadotropin dose used, stimulation time and, cost of the therapy.